Penerapan Metode Dempster Shafer Dalam Mendiagnosa Penyakit Faringitis - Hasibuan, Pauji Safri; Batubara, Muhammad Iqbal (STMIK Budi Darma, 2019)
Pharyngitis is an inflammatory disease that attacks the throat or upstream of the esophagus. Sometimes also called a sore throat. This inflammation can be caused by a virus or streptococcus bacteria. Viral infections are usually the cause of colds and influenza which then results in inflammation of the throat. Dempster Shafer Theory is a mathematical theory for proof based on belief functions and plausible reasoning, which is used to combine separate pieces of information (evidence) to calculate the probability of an event